ANALISISPENGARUHMODAL INTELEKTUAL TERHADAPKINERJAPERUSAHAAN (STUDI PADA PERUSAHAAN SEKTOR CONSUMER GOODS INDUSTRY YANG TERDAFTAR DI BEI PADA TAHUN 2011-2013) - Prasetyo B51108028, Nugroho Dwi (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
This study aims to determine the relationship between the Intellectual Capital to the company’s performance. IC is the independent variable and the company's financial performance as the dependent variable. The objects in this study were 33 on sector Consumer Goods Industry companies listed on Indonesian Stock Exchange (IDX) in 2011-2013. This study used Pulic models (Value Added Intellectual Coefficient – VAICTM) in measuring the efficiency of the IC component; Value Added Capital Coefficient (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA) and Partial Least Square method (PLS) was used as a tool to examine the relationship between financial performance VAICTM which was constructed by three financial ratios, namely: ROE, EPS and NPM. The result indicated that the Intellectual capital (IC) has a positive effect on company's financial performance as evidenced by the results of testing three hypotheses are : IC positively effects on the company's financial performance ; IC positively effects on the company's future financial performance ; and Rate of Growth of Intellectual Capital (ROGIC) does not have a positive effect to the company's future financial performance. Keywords: Intellectual Capital (IC), Company’s Performance (PERF) and Partial Least Square (PLS)